Універсальна модель регулювання частоти і потужності в об’єднаних енергосистемах - Kulyk М.M.; Dryomin V.P. (General Energy Institute of the National Academy of Sciences of Ukraine, 2013)
Elaboration of a general-purpose mathematical model with corresponding software and information complex (SIC), allowing study of the automatic frequency and power control (AFPC) systems, built on the basis of generator regulators, controllable loads and their combinations, had been proved to be a necessity.The general-purpose model of frequency and power regulation in united power systems with the above mentioned facilities was elaborated and studied. The model is constructed on the basis of the most precise system character equations and the equations, describing the influence of systematic frequency and power changes upon the power system objects (generators, load, regulators). It allows for the non-linear constraints, that are inherent to regulators (operating speed, maximum power, the dead zone). The model was synthesized in the canonical form, allowing describing the power system as the aggregate one as well as detailing it to a specific generator and a specific load.The digital modeling, carried out by means of the specially elaborated SIC with due facilities, revealed the necessity of considering the above mentioned technological restrictions at the study of the automatic frequency and power control, as the ignorance of them leads to serious mistakes and even incorrect results, presented in the most part of existing publications.The digital modeling of the automatic frequency and power control systems’ processes in the systems with different regulators under conditions of the Ukrainian UPS proved the requirements as to operating speed to be met with confidence only by the HPP generators and the controllable loads at the water pump systems. The oil and gas units with the marginal productivity of up to 6%/min and all the coal-fired units require a multiple increase in backup capacity of the secondary regulation to meet the requirements of marginal extent of the regulatory process.The combined use of primary regulator generator regulators and high-speed controllable loads at heat pump equipment in the AFPC systems completely satisfy both national and international requirements as to such systems.